(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This essay highlights research conducted by the UNESCO Institute for Lifelong Learning (UIL) and focuses on the intersection of top-down and bottom-up approaches to recognition, validation, and accreditation (RVA) systems to ensure they are accessible, equitable, and responsive to the diverse needs of displaced individuals. Using cases from Mexico, Germany, Sri Lanka, and Kenya, the essay demonstrates how legal frameworks, community-driven efforts, and multi-stakeholder partnerships contribute to more inclusive RVA practices. The findings suggest that bridging top-down policy initiatives with bottom-up practices requires collaborative platforms, co-designed frameworks, targeted pilot programs, continuous feedback loops, and capacity-building efforts, thus allowing policymakers and practitioners to create more adaptive and inclusive RVA systems that empower migrants and refugees to leverage their skills and experience for meaningful educational and employment opportunities. The paper points out that migration and displacement are complex, multi-faceted topics that cut across economic, social, political and educational spheres, and that a united front that connects stakeholders at different levels will be significant in ensuring that individual migrants and refugees are truly able to access and complete RVA processes.